Kontroversi Keputusan Seorang Pemimpin: Analisis Hermeneutik Kisah Barak Berdasarkan Hakim-Hakim 4:6-9 - Pattinaja, Aska Aprilano; Kiamani, Andris; Matulatuwa, Barsalin Martha (Program Pascasarjana UKIM, 2024)
Judges 4:6-9 records God's call to Barak to lead the attack against Sisera, with the possibility of receiving the honor of victory. Ironically, however, this honor was ultimately denied to Barak because of the controversy surrounding his decision. Most previous studies have focused on Deborah's role, neglecting the significance of Barak's story. This study explores the key factors that led to Barak's controversial decision to provide lessons for any leader entrusted with responsibility by God. Using a descriptive qualitative approach to understand and describe the phenomenon in depth through non-numerical analysis as well as hermeneutic study, this study found three main factors that contributed to Barak's failure: first, his doubts based on real conditions; second, his reliance on human assurance; and third, his lack of trust in God's power. Barak's failure serves as a valuable warning to today's leaders to recognize weaknesses without losing optimism and confidence in the potential that lies within their God-given responsibilities.